De la prédation à l’affection dans la biosphère - Marcel Delpoux (Caliban: French Journal of English Studies)
From the early period of the evolution of the biosphere to the present day, predation has always existed, instinctive, blind and more or less violent. In some lineages, particularly animal and chiefly human ones, that predation was belatedly accompanied with intra- or interspecific, instinctive, or reasoned and conscious behaviours, ranging, in particular, from affection to love between humans and non-humans. That new aspect of things, an immaterial, original characteristic of the biosphere, increases diversity linked with the emergence and development of intelligence and cognitive capacities. It is also a reference and a hope to try to reduce mankind’s violence, strongly increased by the recent evolution of “modern” societies.